Bioconversion of palm kernel meal for aquaculture: Experiences from the forest region (Republic of Guinea) - Marc Legendre; Saurin Hem; Sékou Toure; Cé Sagbla (Advances in Aquaculture and Fisheries Management, 2020)
Proteins and fats locked in palm kernel meal cannot be used directly by fishes. Enzyme from maggots (HERMETIA ILLUCENS larvae) lyses and extracts those nutrients which are consumed as food. Biomasses of maggots produced can be used to feed fishes. This innovation opens a new hope for many African countries where so much agro-industry by-products exist such as palm kernel meal, groundnut meal, cotton seed meal. The different aspects involved in this discovery are explained before the sequence of processes up to final discovery is described.